1995
DOI: 10.1111/j.1749-6632.1995.tb17464.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Receptor Function in the Mammalian Central Nervous Systema

Abstract: The diversity of neuronal nicotinic receptors (nAChRs) in addition to their possible involvement in such pathological conditions as Alzheimer's disease have directed our research towards the characterization of these receptors in various mammalian brain areas. Our studies have relied on electrophysiological, biochemical, and immunofluorescent techniques applied to cultured and acutely dissociated hippocampal neurons, and have been aimed at identifying the various subtypes of nAChRs expressed in the mammalian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 64 publications
1
99
0
3
Order By: Relevance
“…Receptors composed of a7 subunits are known to present low affinity for [ 3 H]-(-)-nicotine in binding studies, but a high efficacy for (-)-nicotine in single channel conductance studies (15,16). On the other hand, these receptors exhibit low efficacy for DMPP and carbachol (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptors composed of a7 subunits are known to present low affinity for [ 3 H]-(-)-nicotine in binding studies, but a high efficacy for (-)-nicotine in single channel conductance studies (15,16). On the other hand, these receptors exhibit low efficacy for DMPP and carbachol (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Mecamylamine (10 nM), a potent nAChR inhibitor composed of a3ß4 subunits (15,19), blocked with higher efficiency the nicotine-induced contraction of vasa deferentia isolated in the afternoon when compared to those isolated at night. On the other Figure 4 -Effect of endogenous and exogenous melatonin on mecamylamine (10 nM) inhibition of the noncumulative concentration-effect curve for nicotine in the prostatic portion of the rat vas deferens.…”
Section: Discussionmentioning
confidence: 99%
“…Since successful clonings of neuronal nAChR subunit genes (α2−α8, β2−β4) more than 20 years ago, many studies have demonstrated that functional nAChRs could be formed by heterologous expressions of α7 subunit alone [9-11, 35, 39] and that there are homomeric α7 nAChRs expressed in neuronal systems [40][41][42][43] . However, over the years, some experimental observations supported the notion that there may be heteromeric receptors containing α7 subunits in combination with other neuronal nAChR subunits [44][45][46][47] .…”
Section: Channel Properties Of α7 Nachrs Expressed In the Kxα7r1 Cellsmentioning
confidence: 99%
“…Considering that neuronal nAChRs have been found presynaptically controlling the release of numerous neurotransmitters and on postsynaptic neurons, such a chemical network will have a strong impact on establishing the overall degree of activity of a given circuitry in the brain (see Albuquerque et al, 1995).…”
Section: Serotonin (5-ht) As a Putative Endogenous Nicotinic Aplmentioning
confidence: 99%